As fábricas de tecido do estreito no Porto, segundo o inquérito de 1814 - Soeiro, Teresa (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Based on the governmental Enquiry of 1814, this paper focuses on the relevance of the ribbonweaving industry of Oporto from the second half of the 18th century to the first half of the 19th century. Manufacturers, establishments, means of production, working conditions and workforce (particularly the persistent sexual discrimination) are analysed.